1975
DOI: 10.1002/bit.260171105
|View full text |Cite
|
Sign up to set email alerts
|

Substrate inhibition kinetics: Phenol degradation by Pseudomonas putida

Abstract: SummaryA pure culture of Pseudomonas putida was grown in both a batch and continuous culture using phenol as the limiting substrate. Of two substrate inhibition models examined, the Haldane function was found to statistically best describe the kinetics. The applicable kinetic constants were either measured ( p~, K I ) or estimated ( K s ) from the experimental data. Particularly in the continuous culture, wall growth was found to exert significant effects on the broth biomass concentration and phenol conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
2
5

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(147 citation statements)
references
References 17 publications
9
131
2
5
Order By: Relevance
“…Thus, it is observed that as the initial phenol concentration increased the duration of the lag phase increased; and thereby, prolonging the biodegradation time as a result of decrease in the rate of degradation. This observation is supported by the earlier works of Andrews (1968), Hill and Robinson (1975), Collins and Daugulis (1997), and Oboirien et al (2005). According to Prpich and Daugulis (2005), the rate of substrate consumption was suggested to be the most important measure of microbe performance.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, it is observed that as the initial phenol concentration increased the duration of the lag phase increased; and thereby, prolonging the biodegradation time as a result of decrease in the rate of degradation. This observation is supported by the earlier works of Andrews (1968), Hill and Robinson (1975), Collins and Daugulis (1997), and Oboirien et al (2005). According to Prpich and Daugulis (2005), the rate of substrate consumption was suggested to be the most important measure of microbe performance.…”
Section: Resultssupporting
confidence: 82%
“…A variety of techniques involving physical, chemical and biological methods have been used for the removal of phenol from industrial effluents and contaminated The meta-cleavage pathway for the biodegradation of phenol A= Phenol, B= Catechol, C= 2-Hydroxymuconic semialdehyde, D= 2-Hydroxymuconate, E= 2-Oxo-4-enoadipate, F= 2-Oxo-penta-4-enoate, G= Pyruvate, H= Acetaldehyde, I= Acetyl Co A, E1= Monooxygenase phenol hydroxylase, E2=Catechol-2, 3-dioxygenase, E3= Hydrolase, E4= Dehydrogenase, E5= Isomerase, E6= Decarboxylase, E7= Hydrotase, E8= Aldolase waters with bioremediation receiving the most attention due to its environmental friendliness, its, ability to completely mineralize toxic organic compounds and of low-cost (Kobayashi and Rittman, 1982;Prpich and Daugulis, 2005). Microbial degradation of phenol with different initial concentrations ranging from 50-2000 mg/L have been actively studied using shake flask, fluidized-bed reactor, continuous stirred tank bioreactor, multistage bubble column reactor, air-lift fermenter and two phase partitioning bioreactor methods (Bettmann and Rehm, 1984;Sokol, 1988;Annadurai et al, 2000;Reardon et al, 2000;Ruiz-ordaz et al, 2001;Oboirien et al, 2005;Prpich and Daugulis, 2005;Saravanan et al, 2008) and these studies have shown that phenol can be aerobically degraded by wide variety of fungi and bacteria cultures such as Candida tropicalis (Ruiz-ordaz et al, 2001, Chang et al, 1998Ruiz-ordaz et al, 1998); Acinetobacter calcoaceticus (Paller et al, 1995); Alcaligenes eutrophus (Hughes et al, 1984;Leonard and Lindley, 1998); Pseudomonas putida (Hill and Robinson, 1975;Kotturi et al, 1991;Nikakhtari and Hill, 2006); and Burkholderia cepacia G4 (Folsom et al,1990, Solomon et al,1994. In microbial degradation of phenol under aerobic conditions, the degradation is initiated by oxygenation in which the aromatic ring is initially monohydroxylated by a mono oxygenase phenol hydroxylase at a position ortho to the pre-existing hydroxyl group to form catechol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(l), (4), and (S)] or four [eqs. (2) and (3)] kinetic constants. The graphical methods (linearized forms such as Lineweaver-Burk, Edie plots, etc.…”
Section: Determination Of Biokinetic Constants Pmax K Ki and Kmentioning
confidence: 99%
“…Phenol is a reasonably common wastewater contaminant (Li and Humphrey, 1989), which has been found to be either toxic or lethal to fish and most types of microorganisms at relatively low concentrations (Hill and Robinson, 1975). Studies on microbial means of treating or removing phenols dates back to at least three decades.…”
Section: Introductionmentioning
confidence: 99%